Governance and Upgrading Product: Study of Kopi Kenangan and Starbucks - Ica Cahayani; Imam Fadhil Nugraha; M. Andi Pasha (Journal of World Trade Studies, 2021)
This study was conducted to explain, first, the form of governance and upgrading between two coffee companies, namely Kopi Kenangan and Starbucks. Second, it would explain in detail the components of Starbucks governance that could be applied to Kopi Kenangan considering that Kopi Kenangan had a fairly high coffee quality but still requires development in terms of governance. This study uses the theory of governance and upgrading and the research method used is in-depth interviews and narrative review to explain and analyse the governance and upgrading of Kopi Kenangan and Starbucks. Based on the research, results showed that Starbucks Coffee had reached the world market, this was due to Starbucks governance which had undergone a commodification process. Starbucks was not only able to create a value chain in coffee-based beverages but could also reach the level of sustainability standards. Starbucks had good governance externally and internally. While Kopi Kenangan was a coffee company with distinctive coffee standards and must be able to compete with market standardization in the current era of globalization. Thus, Kopi Kenangan must be able to have governance like Starbucks which had a chain and high standards. In the context of upgrading analysis, the two coffee companies tended to have the same upgrading.